2020
DOI: 10.5455/medarh.2020.74.450-454
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Interstitial Lung Disease: Measuring and Predictive Factors Among Patients Treated in Rehabilitation Clinics at Royal Medical Services

Abstract: Introduction: Autoimmune diseases have increasing importance in modern medicine and cover increasing areas of medicine including rheumatoid arthritis interstitial lung disease. Aim: The main aims of this study are to evaluate the association of some autoimmune variables in patients with rheumatoid arthritis interstitial lung disease. Methods: A retrospective study was conducted from files of patients with rheumatoid arthritis interstitial lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In this study, assessment of the clinical characteristics of patients in the RA and RA-ILD cohorts showed that patients with ILD were more likely to be older, male, have a history of COPD, and have more prominent RA [16][17][18][25][26][27][28][29] , we confirmed baseline COPD 30 , and baseline moderate-to-high CDAI score, and CRP > 5 mg/L as risk factors. Although smoking is an established risk factor for RA-ILD 25,31 , in our analysis, differences in baseline smoking prevalence were not significant based on statistical testing. However, it should be noted that identification of smoking exposures in patient data www.nature.com/scientificreports/ is limited by missingness, and there may have been a large proportion of false negatives, which would limit reliability.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In this study, assessment of the clinical characteristics of patients in the RA and RA-ILD cohorts showed that patients with ILD were more likely to be older, male, have a history of COPD, and have more prominent RA [16][17][18][25][26][27][28][29] , we confirmed baseline COPD 30 , and baseline moderate-to-high CDAI score, and CRP > 5 mg/L as risk factors. Although smoking is an established risk factor for RA-ILD 25,31 , in our analysis, differences in baseline smoking prevalence were not significant based on statistical testing. However, it should be noted that identification of smoking exposures in patient data www.nature.com/scientificreports/ is limited by missingness, and there may have been a large proportion of false negatives, which would limit reliability.…”
Section: Discussionsupporting
confidence: 69%
“…A higher proportion of patients with RA–ILD had Medicare insurance when compared with the RA cohort; this can be at least partially explained by the age difference, as a larger proportion of patients with RA–ILD were over the age of 65 when compared with the RA cohort. Potential risk factors for RA–ILD were further analyzed by a Cox regression model and, in addition to older age and seropositivity, which are already established risk factors 16 18 , 25 29 , we confirmed baseline COPD 30 , and baseline moderate-to-high CDAI score, and CRP > 5 mg/L as risk factors. Although smoking is an established risk factor for RA–ILD 25 , 31 , in our analysis, differences in baseline smoking prevalence were not significant based on statistical testing.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…According to relevant literature, the incidence of RA is the highest in systemic connective tissue disease mostly in women aged 35–55 years old, with the incidence as 0.49%, and the incidence and disability rate of RA increase with age [ 4 ]. According to statistics, the number of patients with RA accounts for about 0.99% of the global population, with the prevalence rate in China at about 0.29%, and the ratio of male to female morbidity is about 1 : 2.4 [ 5 ]. Skielta Mattias et al [ 6 ] have noted that the 4–9 years of mutilation rate is about 59.99% if RA patients do not receive timely treatment, and the disability rate over 25 years is 89.99%, which seriously affects the health of patients.…”
Section: Introductionmentioning
confidence: 99%